PENGEMBANGAN LKPD BERBASIS GUIDED WRITING UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEGAK BERSAMBUNG SISWA KELAS II SD - Salsabila, Dwi Cahya; Kartika Dewi, Galuh; Khusni Mubarok, M. (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The reason for conducting this research is the problems faced by grade II elementary school students, namely students are less skilled in writing using cursive letters, because there has not been application of special learning media to practice cursive writing and lack of guidance from teachers in practicing writing using cursive letters. This research aims to improve students cursive writing skills through the utilization of LKPD to write upright with friends together. This research applies the research and development method with the ADDIE model. The data collection techniques used include validation from media and material experts, as well as tests. Instruments used in data collection this research is in the form of a media and material expert validation questionnaire, as well as a cursive writing skills test. And the results of this study were calculated using data analysis techniques in the form of media and material feasibility analysis, as well as the N-Gain test. The results showed that the media used obtained an assessment from the media expert of 93%, while the assessment from the material expert 97%, and the final result of validation is 95% with the criteria